Prescribed burning in Sweden - Hermanson, Virginia (2020)
The application of prescribed burning as a conservation measure is a growing trend in Fennoscandia to restore forest landscapes that have been heavily impacted by humans. Both intensive management for forestry and wildfire suppression altered the disturbances shaping boreal forests over the past centuries, which seen today are more homogenous, lacking dead wood and deciduous trees, and are in the successional process towards darker Picea abies (Norway spruce) dominated stands. Prescribed burning in Sweden is intended to improve biodiversity by thinning Pinus sylvestris (Scots pine) stands and highly reducing the presence of spruce, creating high volumes of sun-exposed dead wood, fire scarred trees, and soil conditions benefitting deciduous trees. The purpose of this project was to quantitatively evaluate the effectiveness of prescribed burning in producing these changes and features. Eleven prescribed burn sites were surveyed in fall 2019 for targeted structural values, and meteorological information was extracted from online national databases and from summary reports describing the burns. Field data was compared with meteorological conditions through correlation analysis to identify clear trends between burning conditions and the outcomes of the burns. The results and field observations indicated that the burns were very low intensity, and in most cases, did not result in the targeted structural changes. Mortality rates were particularly low in older stands, especially in those without spruce, as the burns were most effective at killing spruce and small diameter pines. This highlights the importance of stand structure and choice of stand in achieving successful burn outcomes. Correlations between meteorological variables and outcome variables indicated that burning needs to take place when conditions are warmer and drier to achieve the desired structural values. Prescribed burning operations, however, may be limited to low intensity burning due to concerns around safety, values at risk, public opinion, as well as typical climate. Further research is needed to determine the characteristics of sites that this type of low intensity prescribed burning is appropriate for to achieve conservation targets, though this initial review indicated greater success in younger and more heterogeneous stands. Manual work done in preparation for prescribed burning could improve results. On-site weather and intensity data, as well as biodiversity surveys are needed to better understand the link between burning conditions and the outcomes in different types of stands, and what levels of targeted values need to be reached to provide habitat improvements and benefits to biodiversity.